Mesenchymal Stem Cell Isolation from Human Umbilical Cord Tissue: Understanding and Minimizing Variability in Cell Yield for Process Optimization. - Iftimia-Mander, Andreea; Hourd, Paul; Dainty, Roger; Thomas, Robert J. (Biopreservation & Biobanking, 2013)
Human tissue banks are a potential source of cellular material for the nascent cell-based therapy industry; umbilical cord (UC) tissue is increasingly privately banked in such facilities as a source of mesenchymal stem cells for future therapeutic use. However, early handling of UC tissue is relatively uncontrolled due to the clinical demands of the birth environment and subsequent transport logistics. It is therefore necessary to develop extraction methods that are robust to real-world operating conditions, rather than idealized operation. Cell yield, growth, and differentiation potential of UC tissue extracted cells was analyzed from tissue processed by explant and enzymatic digestion. Variability of cell yield extracted with the digestion method was significantly greater than with the explant method. This was primarily due to location within the cord tissue (higher yield from placental end) and time delay before tissue processing (substantially reduced yield with time). In contrast, extraction of cells by explant culture was more robust to these processing variables. All cells isolated showed comparable proliferative and differentiation functionality. In conclusion, given the challenge of tightly controlled operating conditions associated with isolation and shipping of UC tissue to banking facilities, explant extraction of cells offers a more robust and lower-variability extraction method than enzymatic digestion.